Restoran Indonesia dengan Desain Modern Bermotif Kawung - Kumala, Eni Sartika; Purwoko, Gervasius Herry; Prihatmanti, Rani (KREASI, 2015)
With the progress of modern and current era, Indonesia has seen a steady growth, weather in its economy, technology and its society’s lifestyle. This progress has been centered aroundthe big cities in Indonesia, one of which is Surabaya. People here are keeping up with the progress and modernity, especially in economy and lifestyle. Surabaya have various new businesses, specifically in culinary field, which targets the Surabaya market that’s prioritize on lifestyle, considering that having a meal together and hanging out with family and friend as an important lifestyle. This culinary business needs to be supported by some important factors such as location, quality of food and the design of the restaurant. Niki Sae restaurant is located in the residential area of East Surabaya with upper middle class inhabitant (Ir. H. Soekarno-Hatta street and Dharmahusada Indah I street) which caters Indonesian cuisine with natural modern concept, also indoor-outdoor restaurant system. The problem it faces is the desire for design concept that is modern by selling particular Indonesian cuisine, hence the design combines Indonesian elements in a natural modern restaurant concept.